Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Enhanced Photocatalytic Paracetamol Degradation by NiCu-Modified TiO2 Nanotubes: Mechanistic Insights and Performance Evaluation - Pinna, Marco; Zava, Martina; Grande, Tommaso; Prina, Veronica; Monticelli, Damiano; Roncoroni, Gianluca; Rampazzi, Laura; Hildebrand, Helga; Altomare, Marco; Schmuki, Patrik; Spanu, Davide; Recchia, Sandro (Nanomaterials, 2024)
Anodic TiO2 nanotube arrays decorated with Ni, Cu, and NiCu alloy thin films were investigated for the first time for the photocatalytic degradation of paracetamol in water solution under UV irradiation. Metallic co-catalysts were deposited on TiO2 nanotubes using magnetron sputtering. The influence of the metal layer composition and thickness on the photocatalytic activity was systematically studied. Photocatalytic experiments showed that only Cu-rich co-catalysts provide enhanced paracetamol degradation rates, whereas Ni-modified photocatalysts exhibit no improvement compared with unmodified TiO2. The best-performing material was obtained by sputtering a 20 nm thick film of 1:1 atomic ratio NiCu alloy: this material exhibits a reaction rate more than doubled compared with pristine TiO2, enabling the complete degradation of 10 mg L−1 of paracetamol in 8 h. The superior performance of NiCu-modified systems over pure Cu-based ones is ascribed to a Ni and Cu synergistic effect. Kinetic tests using selective holes and radical scavengers unveiled, unlike prior findings in the literature, that paracetamol undergoes direct oxidation at the photocatalyst surface via valence band holes. Finally, Chemical Oxygen Demand (COD) tests and High-Resolution Mass Spectrometry (HR-MS) analysis were conducted to assess the degree of mineralization and identify intermediates. In contrast with the existing literature, we demonstrated that the mechanistic pathway involves direct oxidation by valence band holes.
CRIS-Team Scopus Importer:2024-10-25
Keywords: emerging pollutants; green chemistry; heterojunction; NiCu bimetallic catalysts; paracetamol; photocatalysis; TiO; water remediation

Photocatalytic reduction and scavenging of Hg(ii) over templated-dewetted Au on TiO2 nanotubes - Spanu, Davide; Bestetti, Alessandro; Hildebrand, Helga; Schmuki, Patrik; Altomare, Marco; Recchia, Sandro (Photochemical & Photobiological Sciences, 2019)
Gold-decorated TiO 2 nanotubes were used for the photocatalytic abatement of Hg(ii) in aqueous solutions. The presence of dewetted Au nanoparticles induces a strong enhancement of photocatalytic reduction and scavenging performances, with respect to naked TiO 2 . In the presence of chlorides, a massive formation of Hg 2 Cl 2 nanowires, produced from Au nanoparticles, was observed using highly Au loaded photocatalysts to treat a 10 ppm Hg(ii) solution. EDS and XPS confirmed the nature of the photo-produced nanowires. In the absence of chlorides and/or at lower Hg(ii) starting concentrations, the scavenging of mercury proceeds through the formation of Hg-Au amalgams. Solar light driven Hg(ii) abatements up to 90% were observed after 24 h. ICP-MS analysis revealed that the removed Hg(ii) is accumulated on the photocatalyst surface. Regeneration of Hg-loaded exhaust photocatalysts was easily performed by anodic stripping of Hg(0) and Hg(i) to Hg(ii). After four catalytic-regeneration cycles, only a 10% decrease of activity was observed.
CRIS-Team Scopus Importer:2019-05-28

Photoinduced release of active proteins from TiO2 surfaces - Song, Yanyan; Hildebrand, Helga; Schmuki, Patrik (Electrochemistry Communications, 2009)
The present work reports on enzyme attachment on and photoinduced release from TiO_2 surfaces. TiO_2 layers (amorphous and anatase) were modified with 3-aminopropyltriethoxysilane (APTES), followed by attachment of vitamin C and horseradish peroxidase (HRP). Using step by step XPS characterization and vis-spectroscopy we show that upon UV illumination the linker chain to the protein can be cut, releasing active HRP into the environment. The head silane group remains attached to the TiO_2 surface. The kinetics of this photoinduced release is significantly faster for the anatase form of TiO_2 compared with amorphous material. The results indicate that UV induced chain scission represents a very versatile tool for payload release from TiO_2 surfaces.
EAM Import::2019-03-12